PERANCANGAN BRAND ACTIVATION DESA WISATA TARUMAJAYA BERSAMA TRAVELOKA DALAM MEMBANGUN RECOGNITION TERHADAP GENERASI Z DI KOTA BANDUNG - Zain Akbarriza, Sania; Maharani Budi, Sri; Ningrum, Nina Nursetia (Telkom University, 2024)
Tarumajaya Village has not maximized its communication messages so that the potential and historical value are less conveyed to its target audience. Therefore, theproblem formulation that will be discussed is how to design communication messages, visuals, and creative media for the needs of brand activation of Tarumajaya TourismVillage in building recognition. The objective to be achieved is to create a communication message as well as visual design and creative media to support the brand activation ofTarumajaya Tourism Village. This research uses a qualitative approach with reference to Moleong’s theory. Data was collected through literature study, observation, interviews,questionnaires. The data was then analyzed through cultural mapping, comparison matrix analysis, SWOT, AOI, and AISAS. The results that have been achieved are the design ofbrand activation in the form of an exhibition event that communicates the historical valueand local wisdom of Tarumajaya Village with the target audience, namely generation Z,especially 17-21 years old in Bandung City. The exhibition will be in partnership with Traveloka and held during the West Java Festival. This concept was chosen becauseTarumajaya Village still needs to build its brand recognition, so a partnership with a wellknown brand and presence in a well-known event can help increase exposure andaudience interest. Through this design, it is hoped that it can be a solution for Tarumajaya Tourism Village in developing a tourism village and introducing it to a wider audiencethrough its unique historical value. Keywords: Tarumajaya Village, history, brand activation, recognition.